Regime of the action in the punishable act of negligent injury (Legal journal - Research in Legal and Social Sciences, 2017)
Since the entry into force of Law 3340/08, which modifies some provisions of the Penal Code (CP), several magistrates consider that the modification inserted in article 113 of the CP has modified the regime of the action in relation to the fact punishable by wrongful injury. In this sense, the judges interpret that the aforementioned punishable act went from being a "crime of private criminal action" to a "crime of public criminal action at the request of a party." The basis of this situation is that, according to the opinion of the magistrates, the modification of article 113 of the CP produced the tacit repeal of art. 17 inc. 3 of the Criminal Procedure Code (CPP). On the other hand, for the Public Ministry, the modification of art. 113 of the CP does not modify article 17 inc. 3 of the CPP, therefore, there are two contrary criteria. With these antecedents, the present investigation proposes to study the problems raised and for this it will start from the following generic question: did the new wording of article 113 of the CP modify the regime of the action with respect to the punishable act of culpable injury?